Estudo do vocabulário do vestuário em documentos setecentistas de Minas Gerais - Gracinea Imaculada Oliveira (2010)
This dissertation aims to describe and analyze the vocabulary of clothing used in the territory of Minas, Brazil, in the 18th century and contrast it with the gender of its owner. Thiswork comprises three chapters and two appendixes.Chapter 1 Theoretical framework - is divided into three sections. The first one presents some general theoretical remarks on language, society and culture. The second section conceptualizes Lexicology and presents some of its fundamental concepts, such aslexical field, word, leme, lexeme and lexia. Terminology is also conceptualized as a branch of Lexicology. In the third section, clothing and some terms of this field are defined, followedby a brief history of Western clothing, dating from Ancient Rome until the 18th century.Chapter 2 Objectives and Method presents both general and specific objectives of this research and describes the method used, and it is divided into three sections. The first of them presents the corpus description, and contextualizes the time of the handwriting of thedocuments; i.e., the 18th century in Minas. The criteria of selection of the inventories used in the corpus are detailed. The second section brings some general aspects of the edition of thedocuments are exposed. The third section, by its turn, informs about the data collection and description. The System of Rational Concepts method used to sort data out is presented,as well as the adjustments done to use it in the research. Moreover, it brings the detailed criteria used to classify the lexemes of the clothing lexical field.Chapter 3 Results is divided into two sections. The first section brings the classification of the lexemes a general and a more detailed one, with definitions and etymology (when it is possible). The second section presents the analysis of the vocabulary ofclothing and contrasts it with her/his once users gender.The section entitled Final Remarks brings the resumption of the main points of the previous chapters and the results of the analysis of the chosen data.The Appendixes edition of the texts brings the edition of the manuscripts out of which the corpus of the research was taken. Moreover, detailed criteria of the edition of the corpus are presented.